Temperature-induced transition of magnetic anisotropy between in-plane and out-of-plane directions in GaMnAs film. (October 2016) - Lee, Sangyeop; Choi, Seonghoon; Bac, Seul-Ki; Lee, Hakjoon; Yoo, Taehee; Lee, Sanghoon; Liu, X.; Furdyna, J.K.
Abstract: We used the Hall effect and magnetization measurements to investigate the temperature dependence of the magnetic anisotropy of a ferromagnetic semiconductor GaMnAs film grown on a (001) GaAs substrate. The Hall effect was systematically measured by applying an external magnetic field within and normal to the film plane. The switching behavior of the magnetization during the reversal process revealed the coexistence of in-plane and out-of-plane magnetic anisotropies in the film. However, these two types of magnetic anisotropies strongly depended on the temperature. Specifically, the out-of-plane anisotropy was dominant in the low-temperature region (i.e., 3–10 K), whereas the in-plane anisotropy became dominant in the temperature region higher than 15 K. This temperature dependent change in the magnetic anisotropy was further confirmed using direct magnetization measurements. Highlights: We investigated the magnetic anisotropy of a GaMnAs film. We performed Hall measurements and direct magnetization measurements to investigate the temperature dependence of magnetic anisotropy. We have found the coexistence of magnetic domains with out-of-plane and in-plane anisotropies in the film. We have found the dominant magnetic anisotropy of the film switched from the out-of-plane to in-plane direction as the temperature increased.